FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI DKI JAKARTA - IVAN SETIADI; MOHAMMAD EDDY ROSYADI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this study is to determine the influence of taxation knowledge, the implementation of e-Filing, the implementation of e-Billing, socialization of regulations, systems and policies, tax office services, and tax sanction on the Individual Tax payer’s Compliance in DKI Jakarta. The sample in this study there were 124 respondents obtained by convenience sampling method. The results of this study indicate that taxation knowledge have an influence on Individual Tax payer’s Compliance. Meanwhile, implementation of e-Filing, the implementation of e-Billing, socialization of regulations, systems and policies, tax office services, and tax sanctionhave no effect on Individual Tax payer’s Compliance